Dietary Fiber Is Inversely Associated With Depressive Symptoms in Premenopausal Women - Li, Di; Tong, Yongqing; Li, Yan (Frontiers in Neuroscience, 2020)
Background An inverse association between dietary fiber intake and depressive symptoms was reported in the general population, but this association is unstudied in midlife women. This study was designed to investigate the association of dietary fiber intake with depressive symptoms in midlife women. Methods Analyses for this cross-sectional study were performed on baseline assessment of the Study of Women’s Health Across the Nation (SWAN). Linear regressions were used to examine the association of fiber intake with Center for Epidemiological Studies-Depression (CES-D) score. Logistic regression and restricted cubic spline analyses were used to examine the association between fiber intake and depressive symptoms (CES-D score ≥ 16). Results A total of 3054 midlife women in our study were stratified into premenopausal women and early perimenopausal women by menstrual bleeding patterns. In premenopausal women, dietary fiber intake was inversely associated with CES-D scores in unadjusted, age-, education-, race/ethnicity-, total family income-, BMI-, sport-, use of antidepressant-, dietary total caloric intake-, SHBG-, and FSH-adjusted linear regression model. The fully adjusted regression coefficient with 95% confidence intervals (CIs) of fiber intakes was −0.146 (−0.235, −0.058) for CES-D score. Fiber intake was inversely associated with depressive symptoms (CES-D score ≥ 16) in crude and fully adjusted logistic regression model. The fully adjusted odds ratios (ORs) with 95% CI of depressive symptoms was 0.483 (0.314–0.745) in quartile 4 compared with quartile 1 for fiber intake. However, in early perimenopausal women, dietary fiber intake was not statistically significantly associated with depressive symptoms. Conclusion Dietary fiber is inversely associated with depressive symptoms in premenopausal women, but not in early perimenopausal women.